Optimizing autologous hematopoietic stem cell transplantation for acute leukemia. (1st November 2021) - Pang, Aiming; Huo, Yingying; Shen, Biao; Zheng, Yawei; Jiang, Erlie; Feng, Sizhou; Han, Mingzhe
Abstract: Autologous hematopoietic stem cell transplantation (ASCT) remains an important postremission treatment for acute leukemia (AL). It is known that some prognostic factors, such as age, cytogenetic and molecular risk stratification, and minimal residual disease (MRD) status, are closely related to clinical outcomes following ASCT. Moreover, there are multiple measurements, including pretransplant treatment, stem cell mobilization and collection, conditioning regimens, and maintenance treatment after transplantation, that can affect prognosis after ASCT. Our clinical practice of ASCT should be better standardized to further improve patient outcomes. This review outlines optimization and quality control measures for ASCT developed at the Institute of Hematology and Blood Diseases Hospital of the Chinese Academy of Medical Sciences, the first established and largest autologous stem cell transplant center in China. These measures will enhance the development of best practices and strategies for AL ASCT therapies, thereby improving patient outcomes. Abstract : Schema for autologous hematopoietic stem cell transplantation in patients with acute leukemia at the Institute of Hematology and Blood Diseases Hospital of Chinese Academy of Medical Sciences.